(3ahGFO GdEQJMGd hfJGFL GdSaQ aj CNHGQ GdbQf GdMGOi YTQs - (3eUWai Hf aJM Gddg GdTGaYqj, GdMehj Ke Gdecqj,J (B1123 (3g` s
(3ChdgG (B:s
(3jHOC HJQLeI GdeMeOjf Ke GdCMeOjf s
(3hgh cJGH MGad JQGLe CYjGf hYdeGA GdbQf GdMGOi YTQ GdgLQis
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B238 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B267s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B115 s
Keywords: (3GdJGQjNs